Optimum Material Removal in Electrical Discharge Machining through Advanced Control Integration of PSoC Microcontroller - Matthias Tiong Foh Thye; Leong Kah Meng; Mohd Azahar Che Abdullah; Jaysuman Pusppanathan; Abd Rahim Mat Sidek; Bentantya Nugroho (Penerbit Universiti Kebangsaan Malaysia, 2025)
Electrical Discharge Machining (EDM) is an advanced non-traditional method for precision material removal using repeated electrical discharges. It utilizes a programmable tool electrode to intricately shape designs. Existing research has highlighted that current EDM control systems are often intricate, sluggish, and costly. In addressing these limitations, there is a notable opportunity to enhance the design of an advanced EDM control system, that is both sophisticated and cost-eff ective. Therefore, the authors proposed an integration of a pulse generator, control system, timer, and fl ushing system using a Programmable System-on-Chip (PSoC) microcontroller to regulate the gap between an electrode a workpiece, fl ushing system, and the overall EDM machining process. The pulse generator algorithm was developed to effi ciently manage Ton and Toff , while the Proportional Integral Derivative (PID) algorithm was employed to uphold the gap between the electrode and the workpiece. Additionally, the timer algorithm was closely associated with the machining process timing. Activation of the second servo pump at 80% of machining was implemented to enhance the fl ushing pressure rate. The EDM-PSoC system was utilized with the experiment conduction at three diff erent current settings (2A, 4A, and 6A) over fi ve periods, and results were compared with the EDM-Existing system. The experimental outcomes revealed a notable increase in Material Removal Rate (MRR), averaging 0.1348 mm3/min at 6A. Furthermore, the EDM-PSoC system demonstrated high consistency in each repetition experiment conducted at lower currents, achieving MRRs of 0.0142 mm3/min at 2A and 0.0560 mm3/min at 4A. Comparatively, the EDM-PSoC system improved the average MRR by 49% compared to the traditional EDMExisting system. The depth of the machined workpiece produced by the EDM-PSoC system was deeper than the EDMExisting system at equivalent time settings. Consequently, the fi ndings indicate that the EDM-PSoC system achieved a higher MRR relative to the conventional EDM procedure, thus improving signifi cantly the system effi ciency.